IMPLEMENTASI ANALISIS JABATAN DALAM RANGKA MENYIAPKAN ORGANISASI AKAMIGAS MENUJU â€œSTEM â€œAKAMIGASâ€ (Studi pada Akademi Minyak dan Gas Bumi, Cepu, Jawa Tengah) - Yunanik, Yunanik (JURNAL BISNIS STRATEGI, 2013)
This case study aims to understand the implementation of job analysis and do job analysis correctlyÂ  and objectively, real, transparent, also comprehensiveÂ  and completeÂ  on all job information in order to prepare the Akamigas organizationÂ  towardÂ  STEM â€œAkamigasâ€.Â Â  This materials case study is consisted by the results of job analysis; they are job description and the job specification.Â  In addition,Â  this case study also illustratesÂ  the constraints which are faced in the implementation of the results of job analysis.This studyÂ  is a qualitativeÂ  research,Â  whereÂ  the data collectionÂ  is done through observation, interviews,Â  and documentationÂ  study, also obtains informationÂ  throughÂ  the Forum Group DiscussionÂ  (FGD) with intent to obtain the results of objective interpretation, so it is able to explore more about the Job Analysis ImplementationÂ  in order to prepare the organization AkamigasÂ  towardÂ  STEM â€œAkamigasâ€.Â  The resultsÂ  of data collectionÂ  were analyzed by qualitative methods using descriptive paradigm. Phenomenological approach which is reinforced by ethnography to find insight that is used to describeÂ  a deep understandingÂ  on the implementation of the analysis by the existing positions.The findingsÂ  of this study indicate; generally, the results of job analysis that ideal has not been achieved, althoughÂ  the employees and leaders understand the significance of job analysis. There are someÂ  errorsÂ  in the implementation of job analysis, includingÂ  process, implementation,Â  evaluation position,Â  individual assessment, development training, job competency,Â  lack of human resources at this time, lack of communication that caused the problem.Â  Furthermore, analyzing all job information toward organization of STEMÂ  â€œAkamigasâ€ throughÂ  a study that is systematicallyÂ  and regularly collectingÂ  all the informationÂ  and facts that relate to a position. The result of study indicate; (1) there are job description which have not been included in old job analysis. (2) there is a change in the organizational structure of college that affect change in the echelon, number of position avalaible and nomenclature changes of organizational units.